PERBANDINGAN TARIF PAJAK EFEKTIF, ASET, RASIO PAJAK, DAN KEPATUHAN STANDAR AKUNTANSI ANTAR PERUSAHAAN (Studi Kasus pada Perusahaan Sektor Pertambangan PT Aneka Tambang Tbk Indonesia dan BHP Group Ltd Australia) - Octaviani, Tarizma Ardis; Kiswara, Endang (Diponegoro Journal of Accounting, 2024)
Tax is a crucial element in a country's economy, playing a vital role as a source of government revenue to support development activities and services to ensure the welfare of the people. This research compares effective tax rates, assets, tax ratios, and compliance with accounting standards between two mining companies, namely PT Aneka Tambang Tbk (Indonesia) and BHP Group Ltd (Australia). Data collection was conducted using documentation methods based on tax information from both companies and literature reviews. The collected data were then analyzed using a qualitative comparative descriptive analysis method with the assistance of Microsoft Excel software.The comparison of effective tax rates shows greater fluctuations in PT Aneka Tambang Tbk compared to BHP Group Ltd. Second, Australian companies consistently have larger assets, reflecting higher operational complexity and internationalization. Third, tax ratios indicate that BHP Group Ltd has a higher level of compliance, indicating better tax management practices. Fourth, differences in compliance with accounting standards reflect a more complex regulatory environment in Indonesia.These findings conclude that BHP Group Ltd has better tax performance compared to PT Aneka Tambang Tbk. Higher and more stable effective tax rates reflect financial stability, higher tax compliance levels, and more effective risk management. These findings underscore the importance of transparent tax strategies and compliance with regulations in the context of cross-country company comparisons.